Pengaruh Kualitas Produk Dan Harga Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Florist Mokka.Id Di Kotagajah - Redo Nur Sanjaya; Nani Septiana; Slamet Tedy Siswoyo (Jurnal Manajemen DIVERSIFIKASI, 2025)
The development of the business world is now increasingly dynamic along with theincreasing public demand for products and services to meet all their needs in Kota Gajahthere are 5 flower bouquet shops. The purpose of this study is to find out whether there is adirect effect of product quality on customer loyalty. Florist Mokka.Id Kota Gajah. To find outwhether there is a direct effect of price on customer loyalty. Florist Mokka.Id Kota Gajah.Mokka.Id Kota Gajah, to find out whether there is a direct effect of price on customersatisfaction Florist Mokka.Id Kota Gajah, to find out whether there is a direct effect ofcustomer satisfaction on customer loyalty Florist Mokka.Id Kota Gajah. Is there an indirectinfluence of product quality on customer loyalty through customer satisfaction FloristMokka.Id kota gajah. This study took a sample of 96 buyers of Mokka.Id Florist Kota Gajah.Data collection used interviews, questionnaires and data libraries using the Validity Test,Reliability Test, Normality Test, Homogeneity Test, Linearity Test and Variable RegressionAnalysis with the Causal Step Method with the program (SPSS 25). There is a direct effect ofProduct Quality on Customer Loyalty, There is a direct effect of Price on Customer Loyalty,There is a direct effect of Product Quality on Costomer Satisfaction. There is a Direct effect of Price on Customer Satisfaction, There is a direct effect of Customer Satisfaction onCustomer satisfaction on costomer loyality